Analisis Qanun Nomor 4 Tahun 2009 Tentang Mekanisme Pengangkatan Kepala Desa Kuala Makmur dan Relevansinya dengan Undang-Undang Nomor 6 Tahun 2014 - Rizky Akbar (Constitutional Law and Siyasah Department, Sharia and Law Faculty, IAIN, 2023)
The enactment of Law Number 6 of 2014 concerning villages and Qanun Number 4 of 2009 concerning Procedures for the Election and Dismissal of Keuchik in Aceh explains the appointment and dismissal of village heads. In the mechanism for appointing the head of kuala Makmur village, there is a polemic in its implementation. This is because, there is a clash between the rules that have been set and those practiced in the field, especially in Kuala Makmur Village. This article is reviewed using the Empirical Juridical research method with a Qualitative approach. The results of the study indicate that the mechanism for appointing the village head of Kuala Makmur is determined through Regional Regulations for a term of office of 6 months to 1 year, but what happens in Kuala Makmur Village exceeds the term of office that should be. Thus, there is a discrepancy in the term of office and authority in sending the head of kuala makmur village as stipulated in Law Law No. 6 of 2014 on villages and Qanun No. 4 of 2009 on the Procedures for the Election and Dismissal of Keuchik in Aceh